'The situation over there really bothers me': Ronald Reagan and the Northern Ireland conflict. Issue 159 (11th July 2017) - Cooper, James
Abstract: The relationship between the Reagan administration and the Northern Ireland conflict is a neglected area of transatlantic history. This article addresses the extent of Ronald Reagan's interest in the Northern Irish conflict and the manner in which other protagonists sought to secure or prevent his involvement. It will examine the president's approach in the context of different views within his administration, the State Department's wish to maintain American neutrality on the issue of Northern Ireland, and the desire of leading Irish-American politicians for the American government to be much more interventionist. These debates coincided with significant developments in Northern Ireland. Therefore, Reagan's contribution to the Anglo–Irish process encapsulates a variety of issues: the Troubles in Northern Ireland during the 1980s, the 1985 Anglo–Irish Agreement and the internationalisation of the conflict before the election of President Bill Clinton in 1993.